Improving Agri-Consulting and Agro-Logistics Services for Farmer Enterprises - Kudratova Iroda Turdibayevna (American Journal of Botany and Bioengineering, 2025)
This article explores the current state and potential improvements in agri-consulting and agro-logistics services for farmer enterprises. As agriculture becomes increasingly technology-driven and market-oriented, the need for professional support in consulting and logistics is growing. This study evaluates existing practices, identifies key challenges, and proposes strategic solutions to enhance the effectiveness and accessibility of agri-services. The findings can contribute to more efficient farming operations and increased rural development.